Letter - Nathans, Nathan, 1883-1937
023_0026_001 INTERNATIONAL TRANSPORTWORKERS' FEDERATION TELEGRAMS: INTRANSFE. AMSTERDAM TELEPHONE 80186 AFFILIATED COUNTRIES: Algeria Argentina Austria Belgium Bulgaria Canada Chinu Cuba Czechoslovakia Danzig Denmark Dutch Guiana Estonia Finland France Germany Great Britain Greece Holland Hungary Iceland India Ireland Italy Japan Luxemburg Morocco New Zealand Norway Palestine Poland Rhodesia Rumania Spain Sweden Switzerland Trinidad Tunis Yugoslavia When will your organization join? Publications: Fascism and Press Report (both fortnightly). Our Ref. 3740 Your Ref. AMSTERDAM. W., HOLLAND VONDELSTRAAT 61 2 December 1936 Sir Walter Citrine, Trades Union Congress General Council, London. Dear Comrade Citrine, Your letter WMC/EAB/138 of the 30th ultimo to hand. Fimmen is abroad at present, but as it happens in a place where he can probably attend to the question raised in your letter. We have duly telephoned with him today, so that you will [NB: if he should have the information with him] no doubt hear personally from him about the matter when he sees you at the I.F.T.U. meeting in Paris next Friday. With kind regards, Yours fraternally, N. Nathans ON BEHALF OF THE INTERNATIONAL TRANSPORTWORKERS' FEDERATION SECRETARY 292/946/23/29